2011
DOI: 10.1002/chem.201102727
|View full text |Cite
|
Sign up to set email alerts
|

Accessing Lipophilic Ligands in Dendrimer‐Based Amphiphilic Supramolecular Assemblies for Protein‐Induced Disassembly

Abstract: Supramolecular nanoassemblies that respond to the presence of proteins are of great interest, as aberrations in protein concentrations represent the primary imbalances found in a diseased state. We present here a molecular design, syntheses, and study of facially amphiphilic dendrimers that respond to the presence of the protein, immunoglobulin G. It is of particular interest that the ligand functionality, utilized for causing the binding-induced disassembly, be lipophilic. Demonstration of binding with lipoph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
29
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 80 publications
0
29
0
Order By: Relevance
“…To test this possibility, we also designed a dendrimer system using dinitrophenyl (DNP) moiety as the hydrophobic ligand functionality, which is complementary to anti-DNP immunoglobulin G (IgG). 118 Indeed, we were able to show that the binding induced disassembly possibility does exist and is likely due to the equilibrium between the unimeric and the aggregated states of the amphiphilic dendrimer assembly. Even though such equilibrium should heavily favour the aggregated state of the amphiphile, a Le Chatelier type effect should be sufficient to funnel the bound dendrons towards the disassembled state.…”
Section: Stimuli Responsive Dendrimersmentioning
confidence: 79%
“…To test this possibility, we also designed a dendrimer system using dinitrophenyl (DNP) moiety as the hydrophobic ligand functionality, which is complementary to anti-DNP immunoglobulin G (IgG). 118 Indeed, we were able to show that the binding induced disassembly possibility does exist and is likely due to the equilibrium between the unimeric and the aggregated states of the amphiphilic dendrimer assembly. Even though such equilibrium should heavily favour the aggregated state of the amphiphile, a Le Chatelier type effect should be sufficient to funnel the bound dendrons towards the disassembled state.…”
Section: Stimuli Responsive Dendrimersmentioning
confidence: 79%
“…Studies with ligand on the hydrophobic side of the dendrimer also resulted in protein-induced disassembly, highlighting the role that the dendrimer-aggregate equilibrium can play in the disassembly process. 91 …”
Section: Protein Sensitive Amphiphilic Dendrimersmentioning
confidence: 99%
“…Therefore, protein-responsive disassembly has been of recent interest. 11 Considering the decisive advantages of multi-stimuli responsive assemblies, we were interested in addressing the challenge of designing a system that not only responds to proteins, but also that would respond only due to the concurrent presence of two different proteins. We demonstrate a versatile new molecular design that allows for such a supramolecular disassembly, illustrated in Figure 1.…”
mentioning
confidence: 99%
“…We have previously shown that micelle-like supramolecular aggregates, from facially amphiphilic molecules, can be disassembled due to a ligand-protein binding event. 11c The disassembly occurs due to the change in the hydrophilic-lipophilic balance caused by the protein binding, i.e . the protein binding causes the equilibrium to shift to the monomeric state of the amphiphile (represented as equilibrium b in Figure 1).…”
mentioning
confidence: 99%
See 1 more Smart Citation